Enhancing natural cycles in agro-ecosystems to boost plant carbon capture and soil storage. Issue 1 (8th July 2021) - Buss, Wolfram; Yeates, Kirsty; Rohling, Eelco J; Borevitz, Justin
Abstract: One of society's greatest challenges is sequestering vast amounts of carbon to avoid dangerous climate change without driving competition for land and resources. Here we assess the potential of an integrated approach based on enhancement of natural biogeochemical cycles in agro-ecosystems that stimulate carbon capture and storage while increasing resilience and long-term productivity. The method integrates plant photosynthesis in the form of (cover) crops and agroforestry, which drives carbon capture. Belowground plant-carbon is efficiently stored as stable soil organic carbon. Aboveground crop and tree residues are pyrolyzed into biochar, which is applied to the soil reducing carbon release through decomposition. Enhanced weathering of basalt powder worked into the soil further captures and stores carbon, while releasing nutrients and alkalinity. The integrated system is regenerative, through enhanced virtuous cycles that lead to improved plant capture, biomass storage and crop yield, the prerequisites for large-scale carbon sequestration along with food security.